Design of BPJS Patient Referral Information System Based on Python Tkinter at Mulia Medika Clinic - Piyyawati Dewi; Yuyun Yunengsih; Falaah Abdussalaam (Lembaga Komunitas Informasi Teknologi Aceh (KITA), 2025)
Digital transformation is still an ongoing process in health service delivery to improve operational performance and service quality. However, BPJS Kesehatan patient referrals are still trapped in administrative bottlenecks. At Mulia Medika Clinic, staff used to handle BPJS patient referrals manually, so that records were prone to errors and delays in obtaining information. We designed, implemented, and tested a desktop-based BPJS referral information system using Python and Tkinter for clinic operations. The development process followed the Waterfall methodology, which consisted of requirements analysis, system architecture design using Context Diagrams, Data Flow Diagrams, Entity-Relationship Diagrams as well as Flowcharts followed by implementation and black-box testing validation. The system will manage patient records, referral processing as well as user administration. Automated features include generating referral letters and producing reports. Testing has proven that this system is accurate and efficient—the manual workload has reduced, data traceability has improved, and continuity in the referral service has been maintained. Results prove operational readiness for clinic deployment to enhance administrative efficiency and precision of the referral data. Currently, it runs standalone without real-time database synchronization; hence workflow integration cannot be achieved. Future versions should have direct connections with both clinic management and BPJS databases to allow seamless data exchange without manual synchronization